Ultrastructural study for the gonadotrophs and somatotrophs of the pituitary gland in aging rabbits of local bread (oryctolagus cuniculus) - Idrees khalaf Thamer (Tikrit Journal of Pure Science, 2023)
Eighteen rabbit of local bread were classified into3 groups A, B, and C Group A were 6 rabbits of age one year Group B were 6 rabbits of age three year Group C were 6 rabbits of age five year The whole animals were accomidated for one month before the study, after that the whole animals were exposed to intensive dose of chloroform and then scarified to obtain the pituitary gland by doing anatomical technique EM processing technique. was done and finally the pituitary gland were examined at the anterior lobe ( pars distalis ) to demonstrate the somatotrophes and gonadotrophes ( FSH and LH ) secreting cells . The present study revealed that somatotrophes and gonado trophes were containing spherical and oval nuclei at one year of age with presence of abundant secretary granules in its cytoplasm associated with Golgi apparatus, these structures were decreased in number and size proportionally with increase of the age of animal at 3 and 5 years .